On Restoring the Centrality of Prudentia (Phronēsis) for Living Well: Pathways and Contemporary Relevance - Ryan, Fáinche ca. 20./21. Jh. (Religions, 2021)
The aftermath of the Second World War saw some radical rethinking in both theology and philosophy on what it is to live well as a human being. In philosophy two of the key thinkers were Elizabeth Anscombe and Philippa Foot. In theology two key thinkers were Thomas Deman, a French Dominican, and somewhat later an English Dominican, Herbert McCabe. A key feature in all four thinkers was a recovery of the work of Aristotle and Aquinas, in particular the concept of phronēsis (prudentia). The paper’s close analysis of the virtue of prudentia demonstrates the insufficiency of modern moral philosophies that are committed to portraying morality as a moral code. A correlative argument is made within theology: the virtue of prudentia fortified by the gift of counsel is central for good Christian living.